Realizacja projektu „człowieka czułego” w Dzienniku wojskowym z 1813 r. i Wspomnieniach mojej młodości Kazimierza Brodzińskiego - Bąkowska, Patrycja (Przestrzenie Teorii, 2023)
The article is devoted to the anthropological “man of feelings” project. This pattern, formed in the 18th century, found its most well-rounded form in Franciszek Karpiński’s work. However, it is worth considering how the “man of feelings” project functioned in the late Enlightenment. This kind of perspective may give an opportunity to show “the long duration” of sentimentalism, defined not only as a literary movement but also a set of anthropological attitudes and ideas, playing a crucial role in Polish culture in the first decades of the 21st century. Kazimierz Brodziński’s literary legacy is one of the most important examples of this phenomenon.